2010
DOI: 10.1089/acm.2009.0693
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Almond Dietary Supplementation on Coronary Heart Disease Lipid Risk Factors and Serum Lipid Oxidation Parameters in Men with Mild Hyperlipidemia

Abstract: These results demonstrated that almond supplementation, in addition to lowering effects on serum levels of CHD lipid risk factors, may contribute to a dramatic change in the relation of lipid risk factors and susceptibility of serum lipids to oxidative modification. This may be due to the distribution of different almond phenolic antioxidants in different components of serum including nonlipoprotein molecules such as serum albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…9 However, similar to our study, Damasceno et al showed no effect on Lp(a) in 18 subjects consuming 50 to 75 g of almonds for 4 weeks, nor did Jalali-Khanabadi et al in 30 subjects consuming 60 g of almonds daily for 4 weeks. 13,24 This study demonstrated a statistically significant shift from pattern A (larger, buoyant LDL-C particles) to pattern B (smaller, dense LDL-C particles) (P 5 .003). This is an unexpected finding because several studies, including a recent study by Parlesak et al, demonstrated decreased small, dense LDL-C levels with increased MUFA consumption.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…9 However, similar to our study, Damasceno et al showed no effect on Lp(a) in 18 subjects consuming 50 to 75 g of almonds for 4 weeks, nor did Jalali-Khanabadi et al in 30 subjects consuming 60 g of almonds daily for 4 weeks. 13,24 This study demonstrated a statistically significant shift from pattern A (larger, buoyant LDL-C particles) to pattern B (smaller, dense LDL-C particles) (P 5 .003). This is an unexpected finding because several studies, including a recent study by Parlesak et al, demonstrated decreased small, dense LDL-C levels with increased MUFA consumption.…”
Section: Discussionmentioning
confidence: 62%
“…17 Our study also demonstrated that adding almonds to statin therapy produced favorable trends in LDL-C and TG. Several other studies have shown significant decreases in LDL-C with the addition of varying amounts of almonds, [9][10][11]13,14,[22][23][24][25] and a meta-analysis by Phung et al reported that almonds strongly trend toward significantly lowering LDL-C. 26 However, to our knowledge, none of these studies focused on subjects already taking statin therapy. In addition, subjects in the present study had a mean baseline LDL-C of 102 6 23 mg/dL.…”
Section: Discussionmentioning
confidence: 94%
“…Their fasting lipid profiles and blood pressure were within the healthy range at baseline. Previous studies that reported significant improvements often included participants with hyperlipidemia 50, 52, 53, 54, 55, 56 or type 2 diabetes. 36, 48, 57, 58 …”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of lipid-neutralizing potential concluded that dietary almonds decrease serum cholesterol, with a strong trend to lower LDL cholesterol [P-trend = 0.05), but do not affect HDL cholesterol (21). The almond trials included in this meta-analysis, as well as others reporting serum lipid concentrations, were conducted in participants who were normolipidemic (22)(23)(24)(25)(26)(27), prediabetic and/or diabetic (26,28,29), obese (30), and/or hyperlipidemic (31)(32)(33)(34), without having low HDL cholesterol at baseline. It seems desirable to investigate the HDL cholesterol-raising potential of almonds in a population that has low HDL cholesterol at baseline (35), such as South Asians.…”
Section: Introductionmentioning
confidence: 99%